Laboratory-numerical investigation of scale effects in granular slides - Kesseler, Matthew (2019)
Granular slides are omnipresent phenomena, occurring in both natural contexts such as avalanches and landslides, and in industrial applications such as blenders, chutes, hoppers, and rotating drums. The correct modelling of these events is paramount to the safety of populations that are at risk from granular slides themselves and other slide-related hazards such as landslide tsunamis. Many granular slides are strongly influenced by their interactions with fluid-phases, such as moisture or entrained snow and ice; nevertheless, this study focuses on "dry" granular slides where the surrounding and interstitial airflow is the dominant fluid phase.